2010
DOI: 10.1172/jci39543
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of TIM-1 blocks the development of disease in a humanized mouse model of allergic asthma

Abstract: Studies in mice and humans have revealed that the T cell, immunoglobulin, mucin (TIM) genes are associated with several atopic diseases. TIM-1 is a type I membrane protein that is expressed on T cells upon stimulation and has been shown to modulate their activation. In addition to a recently described interaction with dendritic cells, TIM-1 has also been identified as a phosphatidylserine recognition molecule, and several protein ligands have been proposed. Our understanding of its activity is complicated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 43 publications
4
38
1
Order By: Relevance
“…Transfected HEK 293T cells were detached with 1ϫ PBS plus 5 mM EDTA 48 h after transfection, washed with 1ϫ PBS plus 5% FBS, and incubated for 1 h with goat polyclonal antisera specific to mTIM-1, TIM-1, TIM-3, or TIM-4 as indicated (R&D Systems) at a concentration of 4 g/ml. Alternatively, cells were incubated for 1 h with human TIM-1 specific mouse monoclonal antibodies (MAbs) ARD5 or AKG7 (4,18,19) as indicated at a concentration of 5 g/ml. Normal goat serum or purified mouse IgG2a (R&D Systems) were used as negative controls.…”
Section: Methodsmentioning
confidence: 99%
“…Transfected HEK 293T cells were detached with 1ϫ PBS plus 5 mM EDTA 48 h after transfection, washed with 1ϫ PBS plus 5% FBS, and incubated for 1 h with goat polyclonal antisera specific to mTIM-1, TIM-1, TIM-3, or TIM-4 as indicated (R&D Systems) at a concentration of 4 g/ml. Alternatively, cells were incubated for 1 h with human TIM-1 specific mouse monoclonal antibodies (MAbs) ARD5 or AKG7 (4,18,19) as indicated at a concentration of 5 g/ml. Normal goat serum or purified mouse IgG2a (R&D Systems) were used as negative controls.…”
Section: Methodsmentioning
confidence: 99%
“…Kim-1 is a member of the immunoglobulin family and is expressed in the surface of activated T cells (CD4 + Th2) (32); therefore, sKim-1 may be involved in the immune response to sepsis and its level is higher than normal in this condition. Previous animal and clinical studies have demonstrated (33,34) that Kim-1 is an inflammation mediator associated with the pathogenesis of asthma and rheumatoid arthritis. A prospective, multicenter cohort study (35) found that Kim-1 peaked at 2 days after cardiac surgery in adults and at 1 day after surgery in children, and that the elevations of Kim-1 were associated with AKI and adverse outcomes in adults.…”
Section: Group a (N=17) Group B (N=21) ------------------------------mentioning
confidence: 99%
“…Anti‐TIM‐1 antibody (Clone RMT1‐10) ameliorates Experimental autoimmune encephalomyelitis (EAE),17 allergic asthma,37 glomerulonephritis38 and corneal allograft rejection 39. In contrast another anti‐TIM‐1 antibody (clone 3B3) enhances T cell proliferation and Th2 effector function 17, 40, 41.…”
Section: Discussionmentioning
confidence: 99%